2020
DOI: 10.1002/iub.2366
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 maintains the methylation of miR‐152‐3p to regulate TMSB10 expression, thereby affecting the biological characteristics of colorectal cancer cells

Abstract: Objective: DNA methyltransferases (DNMTs) take on a relevant role in epigenetic control of cancer proliferation and cell survival. However, the molecular mechanisms underlying the establishment and maintenance of DNA methylation in human cancer remain to be fully elucidated. This study was to investigate that how DNMT1 affected the biological characteristics of colorectal cancer (CRC) cells via modulating methylation of microRNA (miR)-152-3p and thymosin β 10 (TMSB10) expression. Methods: DNMT1, miR-152-3p, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Epidermal growth factor receptor 2 (HER2) and human epidermal growth factor receptor 3 (HER3) belong to the receptor tyrosine kinase (RTK) superfamily, both of which can produce heterodimers to participate in tissue signal transduction, endangering cell differentiation, erosion, differentiation, and migration [ 3 , 4 ]. DNA methyltransferase 1 (DNMT1) is the most abundant methyltransferase in cells, and its role is to maintain DNA methylation [ 5 , 6 ]. The abnormal expression of DNMT1 and HER2 genes may cause the loss of tumor suppressor gene function and the increase of protooncogene activity, which play a key role in the development trend of various malignant tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor 2 (HER2) and human epidermal growth factor receptor 3 (HER3) belong to the receptor tyrosine kinase (RTK) superfamily, both of which can produce heterodimers to participate in tissue signal transduction, endangering cell differentiation, erosion, differentiation, and migration [ 3 , 4 ]. DNA methyltransferase 1 (DNMT1) is the most abundant methyltransferase in cells, and its role is to maintain DNA methylation [ 5 , 6 ]. The abnormal expression of DNMT1 and HER2 genes may cause the loss of tumor suppressor gene function and the increase of protooncogene activity, which play a key role in the development trend of various malignant tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Silencing DNMT1 inhibits the proliferation, migration, and invasion, and induces apoptosis of CRC cells in vitro, and reduces tumor volume and weight in nude mouse. 18 As key regulators that inhibit mRNA translation and promote mRNA degradation, miRNAs are promising inhibitors of DNMT1. Previous studies have confirmed that miR-152 and miR-185-5p can inhibit DNMT1 expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…17 DNA methyltransferase 1 (DNMT1) features prominently in epigenetic modification. 18 A study has demonstrated that DNMT1 is highly expressed in CRC and facilitates the methylation of multiple tumor-suppressive genes. 19 However, the upstream mechanism of abnormal DNMT1 expression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical options for the ClueGO/CluePedia enrichment analysis were set based on a hypergeometric test that is two-sided with p ≤ 0.05, the Benjamini-Hochberg correction, and a kappa score of ≥2 as the primary criteria. Through Cytoscape analysis (GlueGO and CluePedia), we found that members of the GTF3 gene family have a high correlation with metastatic markers such as ABL1 [46,47], WDR6 [48], ARAP1-AS1 [49,50], DNMT1 [51][52][53][54][55], FASN [56,57] (Figure 6D).…”
Section: Pathway Enrichment Analysismentioning
confidence: 99%